Omnidirectional Photodetectors Based on Spatial Resonance Asymmetric Facade via a 3D Self‐Standing Strategy. Issue 16 (28th February 2020) - Pan, Qi; Su, Meng; Zhang, Zeying; Chen, Bingda; Huang, Zhandong; Hu, Xiaotian; Cai, Zheren; Song, Yanlin
Abstract: Integration of photovoltaic materials directly into 3D light–matter resonance architectures can extend their functionality beyond traditional optoelectronics. Semiconductor structures at subwavelength scale naturally possess optical resonances, which provides the possibility to manipulate light–matter interactions. In this work, a structure and function integrated printing method to remodel 2D film to 3D self‐standing facade between predesigned gold electrodes, realizing the advancement of structure and function from 2D to 3D, is demonstrated. Due to the enlarged cross section in the 3D asymmetric rectangular structure, the facade photodetectors possess sensitive light–matter interaction. The single 3D facade photodetectors can measure the incident angle of light in 3D space with a 10° angular resolution. The resonance interaction of the incident light at different illumination angles and the 3D subwavelength photosensitive facade is analyzed by the simulated light flow in the facade. The 3D facade structure enhances the manipulation of the light–matter interaction and extends metasurface nanophotonics to a wider range of materials. The monitoring of dynamic variation is achieved in a single facade photodetector. Together with the flexibility of structure and function integrated printing strategy, three and four branched photodetectors extend the angle detection to omnidirectional ranges, which will be significant for the development of 3D angle‐sensing devices. Abstract : A structure and function integrated printing method is proposed for preparing 3D facade‐based photodetectors between predesigned gold electrodes. Due to the enlarged cross section in the 3D asymmetric rectangular structure, the facade photodetectors with branched geometry achieve omnidirectional angle detection. This strategy provides a general guidance toward novel 3D nanostructured photoelectric devices.